Implementasi Building Information Modeling (Bim) Dalam Analisis Waste Material Tulangan Kolom Pada Gedung LVP Production Indonesia - Chandra, Nanang Aldika; Husni, Hasti Riakara; Bayzoni, Bayzoni; Ashruri, Ashruri (Universitas Lampung, 2024)
The rapid development of information technology, especially in the construction sector, has become an important issue in supporting the country's infrastructure needs to produce increasingly high-quality, integrated, and efficient infrastructure products. Therefore, the utilization of Building Information Modeling (BIM) technology has become an alternative that allows construction stages to be faster and more efficient, especially in minimizing waste material. This research aims to determine the influence of applying BIM concepts in optimizing waste materials for column reinforcement of type 1, type 2, and type 3. The research begins with data collection, structural 3D modeling, reinforcement modeling, input of reinforcement mark schedules, clash detection, Bar Bending Schedule (BBS) output, cutting lists, and waste material analysis. The research results show that the total weight requirement of type 1 column reinforcement is 28,449 kg, type 2 column is 26,390 kg, and type 3 column is 26,784 kg, while the total waste weight of type 1 column is 1,256.41 kg, type 2 is 872.6 kg, and type 3 is 916.14 kg. The waste level of type 1 column reinforcement is 4.42%, type 2 column is 3.31%, and type 3 column is 3.42%. Thus, it can be concluded that type 2 column reinforcement is more effective and efficient compared to type 1 and 3 column reinforcement.